Analysis of the Caribbean wave climate for wave energy harvesting. Issue 14 (12th September 2021) - Lemessy, Kevin G.; Manohar, Krishpersad; Adeyanju, Anthony
Abstract: In this study, the design requirements for a regional wave energy converter are identified from the analysis of 10 years of spectral data provided by nine buoys located across the Caribbean. It indicated that the average significant wave height and wave period in the Caribbean is 1.62 m and 5.91 s, respectively, while the average total theoretical power capable of being absorbed from a wave energy converter is 7.4 kilowatts per meter of surface waves. Devices should be designed to withstand a significant wave height of 19.0 ± 2.8 meters (95% confidence) for a 1 in 100 year return wave. This was determined by performing various extreme wave analyses. Additionally, a design life of 30 years for a device would have a probability of exceedance regarding this return wave as 26%. Using two‐dimensional wave spectra analysis for the resource study, the overall spectral width, directionality coefficient and direction of the maximum directionally resolved wave power for the region are determined to be 0.172, 0.74 and 42°, respectively. It is expected that the combination of these information would improve the viability of a wave energy industry in the Caribbean and advance technological development.